KONSEP DAN AKTUALISASI GOOD GOVERNANCE DALAM PELAYANAN PUBLIK OLEH PEMERINTAH DAERAH - Deden Haria Garmana (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2020)
Good governance concept is an emerging issue in the management of publik admnistration today that emerged in the early 1990s. The system of state governace is important element in a country. In the implementation of regional autonomy, to e able to carry out its functions properly, local gomerments are required to realize goog governance in their respective regions. Good governance relates to how the local goverment both district and ciity as poliisy implementers, both national and local policies. When good governace delas with how local governments implement local level policies it also relates to how local government performance works policies to be implemented by local government.